PROTECTED GEOGRAPHICAL INDICATION FOR AGRICULTURAL PRODUCTS AND FOODSTUFFS – OBJECT OF INTELLECTUAL PROPERTY RIGHT - Constantin, Florentina (Economics of Agriculture, 2012)
In this paper are presented in a synthesis the most important legal aspects regarding the protected geographical indication of the agricultural products or foodstuffs. Also, I emphasized that in the category of intellectual property rights, the right of geographical indications is also found, by which the name of a certain geographical territory is protected, which is used for describing a certain product originating in the respective area. Finally, we point out that the concerns of Romanian farmers or farmers groups, habilitated authorities and institutions for the protection of geographical indications for agricultural products and foodstuffs are mitigated.